The privilege against self-incrimination in England and Canada - Tollefson, EA (1975)
Historically, the concept of protection against testimonial self-incrimination was not an inherent part of the English system of justice. Formal oaths and formal acts to be performed by the defendant were a part of both civil and ecclesiastical trials. The only procedural protection that existed was the requirement that there be "due presentment", i.e., there had to be a specific charge and the solemn accusation before the defendant was required to make any response. When the Church, and subsequently the Star Chamber, adopted an inquisitional procedure, due presentment was by-passed, and there was a great outcry by dissenters. Gradually, the inquisitorial procedure became the focal point of opposition to church and state, and the phrase nemo tenetur setpsum prodere, which formed part of a Statement of law relating to due presentment, was snatched from its context and used as a slogan of the revolution. Common law courts supported the development of the privilege because it provided a means of controlling the jurisdiction of their rivals - the ecclesiastical courts. The fight against the tyranny of kings and bishops was successful, and the privilege became a fundamental rule of English trial procedure. Canada inherited the privilege against self-incrimination from England, but in 1893 the right of a witness not to answer incriminating questions was abolished and replaced by a rule requiring an answer to be given while affording immunity against its use in subsequent proceedings. A comparison of the privilege in the two countries reveals that while the scope of the privilege is essentially the same, its actual operation is very different. Surveys conducted in conjunction with this research showed that the percentage of accused persons choosing not to enter the witness box is substantially higher in Canada than in England. Likewise, the Canadian immunity provision is used much more frequently by witnesses in Canada than is the common law privilege by witnesses in England. The reasons for and the implications of this difference are examined. Continued in thesis ...